Kajian Kemiskinan Pada Tiga Kabupaten/Kota dI Provinsi Maluku - Elsjamina M Latuny; Izaac T Matitaputty (Fakultas Pertanian, Universitas Pattimura, 2020)
Maluku province occupied poverty level number four from 34 provinces in Indonesia. The research aimsto analysis the influence of government spending, private investments and human development indiceson poverty in the provincial districts of Maluku. The data used in this research is time-guided data from2008 – 2018 in three district cities namely Ambon City, central Maluku Regency and Tanimbar IslandsRegency. Data analysis using a panel data regression with Common Effects Model (CEM) method,Fixed Effects Model (FEM), and Random Effects Model (REM). The results of research based onestimation of panel data showed that government expenditure and human development index,significantly influenced the level of poverty in the three districts of the city while private investmentsdid not significantly affect poverty.